Paired Storytelling Learning Model Assisted By Paper Puppet Media On Students' Speaking Skills - Ramadhania, Jerry; Kristiantari, M.G. Rini (Universitas Pendidikan Ganesha, 2020)
Based on the observations made, it was found that there were still many students who had difficulty participating in learning that was related to speaking skills. This study aims to determine the effect of the paired storytelling learning model assisted by the paper puppet media on third-grade students' Indonesian speaking skills. This type of research is quasi-experimental, with a non-equivalent control group design. The population in this study was all groups of third-grade students. This research sample using random sampling. The method of collecting research data is using test and observation methods. The data collection instrument used was an action test in storytelling, which refers to the assessment rubric and the observation sheet. Methods of data analysis using the t-test. Data analysis results obtained significant differences in Indonesian speaking skills between groups of students who were taught with the paired storytelling learning model assisted by paper puppet media and groups of students who were taught using conventional learning in students. So it can be concluded that the Paired Storytelling learning model assisted by the paper puppet media affects the third-grade students' speaking skills of Indonesian.